Visual neglect after right posterior cerebral artery infarction. - Bird, C; Malhotra, P; Parton, A; Coulthard, E; Rushworth, M; Husain, M (2006)
OBJECTIVES: To investigate the characteristics and neuroanatomical correlates of visual neglect after right-sided posterior cerebral artery (PCA) infarction. METHODS: 15 patients with acute PCA strokes were screened for the presence of neglect on a comprehensive battery of cognitive tests. Extra tests of visual perception were also carried out on six patients. To establish which areas were critically associated with neglect, the lesions of patients with and without neglect were compared. RESULTS: Neglect of varying severity was documented in 8 patients. In addition, higher-order visual perception was impaired in 5 of the 6 patients. Neglect was critically associated with damage to an area of white matter in the occipital lobe corresponding to a white matter tract connecting the parahippocampal gyrus with the angular gyrus of the parietal lobe. Lesions of the thalamus or splenium of the corpus callosum did not appear necessary or sufficient to cause neglect, but may mediate its severity in these patients. CONCLUSIONS: PCA stroke can result in visual neglect. Interruption of the white matter fibres connecting the parahippocampal gyrus to the angular gyrus may be important in determining whether a patient will manifest neglect.